Short-term gains in histology knowledge: A veterinary gaming application - Bauman, Eric B.; Gilbert, Gregory E; Vaughan, Greg (PeerJ Preprints, 2017)
Outcomes research exists incorporating non-digital games in veterinary education; however, little research examines outcomes from digital applications. Bauman’s Layered-Learning Model was applied to investigate whether a digital matching game produced short-term knowledge gains in veterinary students. Two groups of students (n1=67; n2=55) practiced the matching game for an hour. A Wilcoxon signed rank test tested for a statistically significant improvement in pre-test/post-test scores. All statistical analyses were done using R. Mean and median pre-test scores were 15 (SD=1.88; IQR: 2) and post-test scores 16 (SD=1.80; IQR: 2). Mean and median pre-test score for Group 2 were 13 (SD=2.30; IQR=2.5) and post-test scores 15 (SD=1.93; IQR=2.5). Both groups increased significantly in post-test scores (P value<.0001). Statistically significant short-term increases of marginal importance in histology knowledge was seen. A greater increase might be seen with quiz revision increasing difficulty and discrimination ability. Further directions should investigate long-term knowledge retention.
Keywords: Veterinary Education; Educational Games; Digital Content; Histology; Digital Native; Gamification; Game-based Learning; Bauman Layered-learning Model